Assistant and auxiliary nurses in crisis times: Earnings and employment following public sector job loss in the 1990s - Marcus Eliason (Institute for Labour Market Policy Evaluation (IFAU), 2011)
This paper studies the earnings and employment consequences of involuntary job loss in Sweden during the crisis years of the 1990s among assistant and auxiliary nurses. These two occupational groups were by far those in the public sector that experienced the largest number of job losses. While public service employment traditionally has been perceived as secure and permanent, Sweden witnessed far-reaching restructuring of the public sector and job loss truly became a reality for public sector employees during these years. The estimates show an immediate annual earnings loss of on average about SEK 12 000 and long-term losses of SEK 5 000 per year. An analysis of the distributional effect shows that the job losses did not affect the whole earnings distribution but mostly the lower part. This suggests that a few bore the whole loss from downsizing but most went on unaffected at least considering earnings and employment. From a policy perspective this points to the importance to early identify these redundant workers and to develop targeted policies improving their situation instead of general policies to all redundant workers.
Keywords: J45; J63; J65; 330; Job displacement; public sector; mass-layoff; earnings losses